Predictors of Environmental Protection and Disaster Management - Adhikari, Kishor; Devkota, Dinesh Chandra (Journal of APF Command and Staff College, 2025)
This study examines the predictors of Environmental Protection and Disaster Management (EPDM) capacity within local governments in Nepal, using the Local Government Institutional Capacity Self-Assessment (LISA) framework developed by the Ministry of Federal Affairs and General Administration. The LISA framework assesses local government capacity across ten domains. The study uses secondary data from the LISA framework, analyzing scores from 544 local bodies. The reliability analysis of the framework resulted in a Cronbach’s alpha of 0.905, indicating a high internal consistency. A linear regression model identified Physical Infrastructure, Social Inclusion, and Collaboration and Cooperation as statistically significant predictors of EPDM capacity, explaining 52% of the variance. These findings underscore the importance of these three areas in building resilience within local governments in Nepal. The study underlines the importance of comprehensive capacity building, whereby improvements in one domain contribute to others, and suggests that targeted investments in infrastructure, inclusive policies, and coordination mechanisms are ways to improve the capacity of local governments to cope with environmental and disaster-related challenges. The LISA framework stands out as a reliable tool for capacity assessment, laying the foundation for further research.